A Spin to Preserve Contrast: Taiwanese Tone Sandhi - Wee, Lian-Hee (Stellenbosch Papers in Linguistics Plus, 2020)
Chain-shifts, particularly circular ones such as the tone sandhi of Taiwanese Min has been a longstanding challenge to which phonologists of various persuasions have attempted. This paper appeals to markedness against contour tones in non-final positions as the point of departure that sets off a chain reaction due to the need to preserve underlying contrasts in surface forms. The account has implications on the historical development and acquisition of the Min tone circle that awaits verification.